Exogenous surfactant as a bridge to prolonged "total lung rest" in severely injured patient during extracorporeal membrane oxygenation - Sklienka, Peter; Maca, Jan; Bursa, Filip; Neiser, Jan; Kula, Roman; Kanova, Marcela; Danek, Tomas; Sevcik, Pavel (Journal of artificial organs, 2018)
We report a case of a 20-year-old male patient suffering from motorcycle accident complicated by rapid development of severe refractory hypoxemia and hypercapnia due to serious bilateral lung contusions and lacerations. Positive pressure mechanical ventilation induced pressure-dependent massive air leak from disrupted pulmonary tissue. Simultaneous implementation of veno-venous extracorporeal membrane oxygenation together with surfactant application allowed prolonged disconnection of patient from mechanical ventilation ("total lung rest" mode). Despite considerable areas of nonaerated tissue on computed tomography prior to the disconnection from mechanical ventilation, almost total functional recovery of lungs was eventually achieved.
Keywords: počítačová rentgenová tomografie; Humans; povrchově aktivní látky; mimotělní membránová oxygenace; syndrom dechové tísně; Surface-Active Agents; mladý dospělý; Lung; výsledek terapie; Total lung rest; Hypoxia; lidé; Respiratory Distress Syndrome; plíce; Extracorporeal Membrane Oxygenation; hypoxie; Male; Extracorporeal membrane oxygenation; Exogenous surfactant; Tomography, X-Ray Computed; Treatment Outcome; Young Adult; mužské pohlaví; Acute respiratory distress syndrome